Association between Thrombophilia and the Post-Thrombotic Syndrome. (9th May 2013) - Rabinovich, Anat; Kahn, Susan R.
Abstract : The post thrombotic syndrome (PTS) is a chronic condition that develops in 20%–40% of deep vein thrombosis (DVT) patients. While risk factors that predispose to the development of venous thromboembolism (VTE) are widely known, factors that influence the development of PTS after DVT have not been well elucidated. Over 10% of the general population is affected by one or more identifiable inherited thrombophilias which have been shown to underlie at least 1/3 of cases of VTE. The various thrombophilias are important risk factors for VTE, but it is unknown whether they also increase the risk for development of PTS. We performed a review of studies that have reported on the association between thrombophilia and the development of PTS in populations of patients with DVT and with chronic venous ulcers. Studies vary with regards to the definition of PTS, study design, follow-up period, and present conflicting results. Based on these results, the question of whether thrombophilia predisposes to the development of PTS remains unanswered.